2019
DOI: 10.21873/invivo.11770
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases (MMP-2,-3,-9) Gene Polymorphisms in Cases of Benign Vocal Fold Lesions and Laryngeal Carcinoma

Abstract: Background/Aim: The matrix metalloproteinases (MMP) play an important role in the physiological and pathological remodeling of tissues including carcinogenesis. The study's aim was to assess the relations between MMP-2(-735C/T), MMP-2(-1306C/T), MMP-9(-1562C/T), and MMP-3(-11715A/6A) polymorphisms, and clinical/morphological manifestation of laryngeal squamous cell carcinoma (LSCC) and benign vocal fold lesions (BVFL). Patients and Methods: Two hundred and seventeen patients with LSCC and BVFL and 458 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…After verification in tumor tissues by IHC and western blot assays, we confirmed that MMP1, MMP9, and MMP17 expression in HCC and CC was increased. These results suggest that gene mutations in TCs might play a pivotal role in the HCC, which has been coincidently reported that MMP9 C/T mutation increases MMP9 overexpression and accelerates the progression of papillary thyroid carcinoma as well as head and neck squamous cell carcinoma (W. Li et al, 2019; Liutkevicius et al, 2020; Roncevic et al, 2019). Furthermore, it was indispensable to predict correlative criticality of SNPs mutations in MMP1, MMP9, and MMP17 through the Polyphen‐2 database, and then, we found that allele shifts of C/T (rs20544) and G/C (rs2250889) in MMP9 were risk factors in HCC.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…After verification in tumor tissues by IHC and western blot assays, we confirmed that MMP1, MMP9, and MMP17 expression in HCC and CC was increased. These results suggest that gene mutations in TCs might play a pivotal role in the HCC, which has been coincidently reported that MMP9 C/T mutation increases MMP9 overexpression and accelerates the progression of papillary thyroid carcinoma as well as head and neck squamous cell carcinoma (W. Li et al, 2019; Liutkevicius et al, 2020; Roncevic et al, 2019). Furthermore, it was indispensable to predict correlative criticality of SNPs mutations in MMP1, MMP9, and MMP17 through the Polyphen‐2 database, and then, we found that allele shifts of C/T (rs20544) and G/C (rs2250889) in MMP9 were risk factors in HCC.…”
Section: Discussionsupporting
confidence: 58%
“…Subsequently, we found expression in HCC and CC was increased. These results suggest that gene mutations in TCs might play a pivotal role in the HCC, which has been coincidently reported that MMP9 C/T mutation increases MMP9 overexpression and accelerates the progression of papillary thyroid carcinoma as well as head and neck squamous cell carcinoma (W. Li et al, 2019;Liutkevicius et al, 2020;Roncevic et al, 2019). (Nagar et al, 2002).…”
Section: Discussionsupporting
confidence: 57%
“…of a recent study revealed that combination of smoking and 6A/6A genotype of MMP3 (-1171 5A/6A) polymorphism are associated with significantly increased odds of LSCC, thus confirming a presumably important role of MMP3 (-1171) 6A/6A genotype in LSCC carcinogenesis (21).…”
mentioning
confidence: 79%
“…A previous study demonstrated that MMP-9 is highly expressed in non-small cell lung, cervical and ovarian cancer, among others, and has become one of the important factors related to cancer metastasis and invasion ( 28 ). MMP-3 protein breaks down a variety of extracellular matrix molecules and cleaves various adhesion molecules, growth factors and other MMPs ( 29 ). MMP-3 can activate MMP-1 and other family members and its overexpression is associated with the growth and metastasis of various cancers, including breast cancer ( 30 ).…”
Section: Discussionmentioning
confidence: 99%